Sudden cardiac death: focus on the genetics of channelopathies and cardiomyopathies - Simona Magi; Vincenzo Lariccia; Marta Maiolino; Salvatore Amoroso; Santo Gratteri (Journal of Biomedical Science, 2017)
Abstract Sudden cardiac death (SCD) describes a natural and unexpected death from cardiac causes occurring within a short period of time (generally within 1 h of symptom onset) in the absence of any other potentially lethal condition. Most SCD-related diseases have a genetic basis; in particular congenital cardiac channelopathies and cardiomyopathies have been described as leading causes of SCD. Congenital cardiac channelopathies are primary electric disorders caused by mutations affecting genes encoding cardiac ion channels or associated proteins, whereas cardiomyopathies are related to mutations in genes encoding several categories of proteins, including those of sarcomeres, desmosomes, the cytoskeleton, and the nuclear envelope. The purpose of this review is to provide a general overview of the main genetic variants that have been linked to the major congenital cardiac channelopathies and cardiomyopathies. Functional alterations of the related proteins are also described.